2022
DOI: 10.1111/mec.16462
|View full text |Cite
|
Sign up to set email alerts
|

Salinity and host drive Ulva‐associated bacterial communities across the Atlantic–Baltic Sea gradient

Abstract: The green seaweed Ulva is a model system to study seaweed-bacteria interactions, but the impact of environmental drivers on the dynamics of these interactions is little understood. In this study, we investigated the stability and variability of the seaweedassociated bacteria across the Atlantic-Baltic Sea salinity gradient. We characterized the bacterial communities of 15 Ulva sensu lato species along 2,000 km of coastline in a total of 481 samples. Our results demonstrate that the Ulva-associated bacterial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 122 publications
2
19
0
Order By: Relevance
“…Yet, within this variability a suite of taxa frequently found on macroalgal surfaces is emerging across studies, including Saprospiraceae, Granulosicoccus, and Flavobacteria [34][35][36]. Earlier studies reported a handful of core bacterial taxa consistently associated with particular populations in a few macroalgal species, including Kelp [37], Agarophyton vermiculophyllum [38], Fucus vesiculosus [28], Ulva australis [39] and Ascophyllum nodosum [40]. However, these studies were limited in scope, focusing on one location at one point in time, often without corresponding sampling of the macroalgae' environment.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, within this variability a suite of taxa frequently found on macroalgal surfaces is emerging across studies, including Saprospiraceae, Granulosicoccus, and Flavobacteria [34][35][36]. Earlier studies reported a handful of core bacterial taxa consistently associated with particular populations in a few macroalgal species, including Kelp [37], Agarophyton vermiculophyllum [38], Fucus vesiculosus [28], Ulva australis [39] and Ascophyllum nodosum [40]. However, these studies were limited in scope, focusing on one location at one point in time, often without corresponding sampling of the macroalgae' environment.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that soil classes are predictive of bacterial and fungal community composition regardless of spatial proximity, natural and cultivated soils are reliably distinct in their microbiomes, and the primary drivers of these microbiome community differences are soil pH and temperature cycles. Van der Loos et al (2022) explored the interplay between environment and host genotype in shaping the stability and variability of microbial composition. Using seaweed-associated bacterial communities along a salinity gradient, they were able to identify a small group of core microbes possibly involved in salinity adaptation of the host.…”
Section: Community Assembly Processesmentioning
confidence: 99%
“…Indeed, U. compressa is found as a monostromatic tubular morphotype in a saline/hypersaline environment and a distromatic foliose form in a low salinity environment, such as estuarine sites [ 141 ]. It is not clear whether these differences can be attributed to a direct effect of salinity or are an indirect effect of salinity associated variation in the microbiome [ 144 ]. No obligate foliose species have been recorded in freshwater ecosystems and tubular morphotypes are found in a broader range of salinities [ 3 , 145 , 146 ].…”
Section: Strategies To Improve Ulva Biomass Yield ...mentioning
confidence: 99%
“…It was hypothesised that this may allow for better protection against increased turgor caused by lower salinity, as this new morphology would allow for the establishment of a more stable microenvironment around Ulva thalli. Contradictory observations were made in the distribution of U. compressa , which more frequently presents the tubular morphotype at high salinity and the foliose morphotype at low salinity [ 141 , 144 ]. Going further, Rybak et al (2018) [ 123 ] hypothesised that an ancestral tubular morphotype carried tolerance and rapid adaptation mechanisms that are independent of morphotype, with these being lost among more recently diverged foliose and/or tubular species, but experimental evidence is unfortunately lacking.…”
Section: Strategies To Improve Ulva Biomass Yield ...mentioning
confidence: 99%
See 1 more Smart Citation